Bridging the knowledge-action gap: A case of research rapidly impacting recreational fisheries policy. (June 2019) - Brownscombe, Jacob W.; Adams, Aaron J.; Young, Nathan; Griffin, Lucas P.; Holder, Peter E.; Hunt, John; Acosta, Alejandro; Morley, Danielle; Boucek, Ross; Cooke, Steven J.; Danylchuk, Andy J.
Abstract: Telemetry is being used to generate an unprecedented level of knowledge on the underwater environment, much of which is relevant to marine policy and management. Yet, examples of telemetry directly informing management practices are still rare or undocumented. Here we describe a case in which fish telemetry data were rapidly incorporated into recreational fisheries policy for Permit ( Trachinotus falcatus ) in Florida. The reproductive strategy of Permit involves forming large aggregations, during which time they are often targeted by recreational anglers. To protect Permit from overfishing, the Florida Fish and Wildlife Conservation Commission established regulations in 2011 to prohibit Permit harvest during May through July, based on knowledge of seasonal Permit reproductive status. However, an acoustic telemetry study initiated in 2016 revealed that spawning aggregations were forming prior to this period, during the month of April. This information had a rapid and definitive impact on fisheries management policy. Given the well-documented difficulties of incorporating new science and information into environmental decision-making, this case provides valuable insights into how the knowledge-action gap may be bridged. Many factors contributed to the rapid uptake of this telemetry-derived knowledge into management, including applied research funding and objectives, integrating managers and stakeholders into the research, rapid dissemination of preliminary data, plus well-established relationships amongst scientists, managers, and stakeholders mediated by a non-government organization, Bonefish & Tarpon Trust. These factors may serve as a basis for researchers and managers seeking to translate new research into management practice, improving research impact and achievement of conservation goals.